Evaluation by a finite element method of the flexibility factor and fixity degree for the base plate connections commonly used - Hamizi, M.; Hannachi, N.E. (Проблемы прочности, 2007)
Using finite element approach, we have determined
the flexibility factor and fixity degree of
connections between a steel column and a reinforced concrete foundation. Two types of connections
are studied. The first one consists of a
base plate welded to the end of column and attached
to the reinforced concrete foundation by
two anchor bolts. These bolts are placed on the
major axis of the I-shaped section used as column.
In the second configuration, the connection
comprises a base plate and four anchor
bolts placed out side the flanges of the I-shaped
section. Two types of loadings are used, first
connections were subjected to shear force and a
bending moment, in the second case, the connections
were subjected to shear force, a bending
moment and an axial compressive force. To
take into account the real behavior of these connections,
an approach treating of the contact-
friction problem between the base plate
and the concrete foundation is retained. The
method of approach is based on a unilateral contact
law in which a Coulomb friction is added.
The numerical resolution is ensured by the refined
Lagrangian method. The moments-rotations
curves, the flexibility factor according to
the distance of the top of base plate curves are
drawn. The fixity degrees of the connections
are determinate and their influence on the loads
and deformations are evaluated. Із використанням скінченноелементного підходу визначено значення коефіцієнта
гнучкості та степеня стійкості вузлів з ’єднання стальної балки із
залізобетонною основою. Досліджено два типи з ’єднань: у першому стальна
опорна пластина з привареною до неї вертикальною балкою кріпиться до
залізобетонної основи двома анкерними болтами, які знаходяться на осі
симетрії двотаврової балки, у другому - чотирма болтами. Навантаження
прийнято двох типів: перше з ’єднання зазнавало дії перерізувальної сили і
згинального моменту, друге - перерізувальної сили, згинального моменту та
осьової сили стиску. Реальну поведінку цих з ’єднань описували за допомогою
підходу, який враховує умови контакту та тертя між опорною плитою
і залізобетонною основою. Підхід базується на однобічності залежності для контактної задачі з кулонівським тертям. Для підвищення точності
числових розрахунків застосовано модифікований метод Лагранжа. Отримано
діаграми в координатах момент-кутове переміщення та коефіцієнт гнуч-
кості-відстань від вершини вертикальної балки до опорної плити. Визначено
вплив степеня стійкості з’єднань на допустимі навантаження і деформації. С использованием конечноэлементного подхода определены значения коэффициента гибкости
и степени устойчивости узлов соединения стальной балки с железобетонным основанием.
Исследуются два типа соединений: в первом стальная опорная пластина с приваренной
к ней вертикальной балкой крепится к железобетонному основанию двумя анкерными
болтами, которые расположены на оси симметрии двутавровой балки, во втором -
четырьмя болтами. Задавались два типа нагружения: первое соединение подвергалось
действию перерезывающей силы и изгибающего момента, второе - перерезывающей силы,
изгибающего момента и осевой силы сжатия. Для описания реального поведения этих
соединений использовался подход, учитывающий условия контакта и трения между опорной
балкой и железобетонным основанием. Подход основан на односторонней зависимости для
контактной задачи с кулоновским трением. Для повышения точности численных расчетов
используется модифицированный метод Лагранжа. Получены диаграммы в координатах
момент-угловое перемещение и коэффициент гибкости-расстояние от вершины вертикальной
балки до опорной плиты. Определено влияние степени устойчивости соединений на
допустимые нагрузки и деформации.